THE USE OF INJECTABLE ANTICOAGULANTS FOR THE MAINTENANCE OF RISKY PREGNANCY IN ANTIPHOSPHOLIPID SYNDROME CARRIERS (CIPEEX, 2022)
THE ANTIPHOSPHOLIPID ANTIBODY SYNDROME (APS) IS A DISEASE CHARACTERIZED BY MAINLY GENERATING ARTERIAL/VENOUS THROMBOSIS AND GESTATIONAL MORBIDITY. IT BELONGS TO THE GROUP OF AUTOIMMUNE DISEASES, WHICH ARE KNOWN BY THE MEDICAL COMMUNITY FOR NOT HAVING A CURE, HOWEVER, IT STRIVES TO SEEK TREATMENTS. THUS, THIS STUDY AIMS TO UNDERSTAND THE EFFECTS OF THE USE OF INJECTABLE ANTICOAGULANTS IN THE CARE OF A HIGH-RISK PREGNANCY IN PATIENTS WITH APS. THIS IS AN INTEGRATIVE REVIEW, CARRIED OUT USING THE PICO TOOL, IN THE MAIN RESEARCH DATABASES SUCH AS GOOGLE SCHOLAR, PUBMED AND SCIELO, WITH THE HELP OF THE DECS AND MESH DESCRIPTORS, CORRESPONDING TO PHOSPHOLIPID ANTIBODY SYNDROME, PREGNANCY, INJECTABLE ANTICOAGULANTS AND HEPARIN WITH PUBLICATION INTERVAL BETWEEN 2017 AND 2022. FROM THE SEARCH, 23 ARTICLES WERE LISTED, IN WHICH, FOR THE MOST PART, SEVERE SYMPTOMS WERE OBSERVED IN RELATION TO BOTH THE FETUS AND THE MOTHER RELATED TO OBSTETRIC APS. IN ADDITION, A CONVERGENCE WAS OBSERVED REGARDING THE SUPERIORITY OF THE POSITIVE EFFECTS TO THE NEGATIVE ONES IN RELATION TO THE TREATMENT UNDER STUDY, WHICH ARE MAINLY BASED ON THE USE OF ASPIRIN OR ASPIRIN COMBINED WITH HEPARIN TO COMBAT THE MAIN SYMPTOMS OF APS DURING PREGNANCY EVEN BEFORE ELUCIDATED. THUS, IT IS CONCLUDED THAT TREATMENT WITH INJECTABLE ANTICOAGULANTS FOR THE MAINTENANCE OF HIGH-RISK PREGNANCIES IN PATIENTS WITH APS IS EFFECTIVE AND PROTECTIVE, BOTH FOR THE PREGNANT WOMAN AND FOR THE FETUS.